2009
DOI: 10.1002/hep.23052
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 prevents fas-induced liver injury through up-regulation of epidermal growth factor receptor #

Abstract: Cyclooxygenase-2 (COX-2)-derived prostaglandins participate in a number of pathophysiological responses such as inflammation, carcinogenesis, and modulation of cell growth and survival. This study used complementary approaches of COX-2 transgenic (Tg) and knockout (KO) mouse models to evaluate the mechanism of COX-2 in Fas-induced hepatocyte apoptosis and liver failure in vivo. We generated Tg mice with targeted expression of COX-2 in the liver by using the albumin promoter-enhancer-driven vector. The COX-2 Tg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…The hepatoprotective effects of induced COX-2 may be attributable to COX-2-derived PGs that assist liver regeneration (Casado et al, 2001) and inhibit inflammation (Yin et al, 2007). In addition, COX-2 prevents secretory phospholipase A 2 - (Bhave et al, 2008) and fas- (Li et al, 2009) induced liver injury. Accordingly, it is not surprising in our study to observe marked upregulation of hepatocyte COX-2 expression after H 2 S treatment.…”
Section: Discussionmentioning
confidence: 97%
“…The hepatoprotective effects of induced COX-2 may be attributable to COX-2-derived PGs that assist liver regeneration (Casado et al, 2001) and inhibit inflammation (Yin et al, 2007). In addition, COX-2 prevents secretory phospholipase A 2 - (Bhave et al, 2008) and fas- (Li et al, 2009) induced liver injury. Accordingly, it is not surprising in our study to observe marked upregulation of hepatocyte COX-2 expression after H 2 S treatment.…”
Section: Discussionmentioning
confidence: 97%
“…In our own view, the reason for these diverse and conflicting observations may not be unconnected with the complex roles of the COX-2-prostanoid pathway in the pathogenesis and pathophysiology of various liver diseases (Hu, 2003). Li et al (2009) have therefore suggested that given the importance of COX-2-derived PGs in several key aspects of liver pathobiology, including hepatocyte survival, liver regeneration, chronic hepatitis, liver injury, and hepatocarcinogenesis, studies are required to detail the mechanisms of COX-2 and PG actions in different liver diseases and animal models.…”
Section: Discussionmentioning
confidence: 98%
“…More- Gene expression between Tg and WT mice at 25 weeks after DEN treatment was compared using RTover, in the same model, this COX-2 transgene accelerates endotoxin-induced acute liver failure 29 but prevents Fas-induced liver injury. 30 The expression of hCOX-2 under the transthyretin promoter produced the highest levels of intrahepatic PGE 2 and induced hepatitis in animals more than 12 months of age, characterized by the activation of NF-B, stimulation of the secretion of proinflammatory cytokines, and enhanced macrophage and lymphocyte infiltration. 28 These data are in agreement with the results we observed in aged animals.…”
Section: Discussionmentioning
confidence: 99%